A condição infantil e o papel do educador em John Dewey - Vieira, Ana Lúcia (2021)
The goal of this dissertation is to investigate the child condition and the role of the educator based on the theoretical construction of the American philosopher and educator John Dewey. The investigation problem was configured as follows: What is the notion of infancy according to Dewey and what role does he attribute to the educator? For this study a qualitative bibliographical research supported by text hermeneutics was used. The first chapter deals with classical education, and verifies how the education of infancy was in the environments of school, family and the very society of the 20th century. In this chapter the possible influences inherited by Dewey are also examined, as well as the influences which funded his progressive theory. Dewey, even contrary to many aspects of the traditional education, especially its scholastic perspective, understanding it as booky, authoritarian and autocratic, has taken some traits of this tradition, considering them fundamental to the new education. In the second chapter, the child's condition is investigated. Dewey states, regarding this, that the child is considered an immature being, but also understands that the very immaturity which allows them to grow, because it is only possible to develop in any dimension in which it hasn't happened yet. For that, the formative experiences must be chained in an experiential continuum, upon which the child puts into play every experience lived, evaluating it só that the following experience is different from the previous. The suggestions, in this sense, need to be coherent for each step of life, respecting the specificities of the infantile being as a starting point for learning. The respect for those specificities involves taking into account aspects such as their interests, desires and the reality in which they live. So that the growth occurs successfully, it is fundamental and irreplaceable of the capacitated conduction of the adult/educator, so as to take advantage of the spontaneous resources from the intatile being, allowing their growth. The role of the educator was the object of investigation in the third chapter. Being the adult/educator the responsible for the infantile conduction, they must be attentive to the pedagogical axis-principles which assure the active participation of the child, which implies coherent conducts, practices and intentionalities for a curriculum which intends to be democratic. In summary, the investigation makes clear how much John Dewey has enhanced the intellectual role of the educator in the sense of contributing for the wide formation of the student.